OKRONOSIS EKSOGEN: PEMBAHARUAN DALAM DIAGNOSIS DAN TATA LAKSANA (Media Dermato Venereologica Indonesiana, 2022)
Exogenous ochronosis is a skin disorder characterized by blue-black or greyish pigmentation with the histological appearance of brownish-yellow deposits of polymerized homogentisic acid (HGA) in the dermis. Exogenous ochronosis is common in dark-skinned individuals, but recent studies have shown that the disease can also occur in ethnic Asians in China, Thailand, and Singapore. The majority of exogenous ochronosis occurs due to the continuous use of topical hydroquinone for a long period of time. The clinical picture of exogenous ochronosis can be different, according to the stage classification. Skin biopsy is an invasve procedure for diagnosing exogenous ochronosis, the standard gold examination with the histological appearance of yellow-brown or green banana-shaped fibres in the dermis. Dermoscopy is one of the latest non-invasive tools that can help diagnose exogenous ochronosis from other hyperpigmented lesions. Dermoscopy examination showed an arciform curvilinear (worm-like pattern) appearance with telangiectasia with grey-blue dots and globules with a caviar-like appearance. Exogenous ochronosis remains a challenging condition to treat. Several therapeutic modalities, such as topical and laser therapy, are available. The European Society of Laser Dermatology (ESLD) recommends laser therapy as the latest therapy in the management of exogenous ochronosis with the principle of fractional ablative modality. However, no single therapeutic modality is consistently satisfactory.